2018
DOI: 10.1128/jcm.01363-17
|View full text |Cite
|
Sign up to set email alerts
|

An Autoimmune Disease-Associated Risk Variant in the TNFAIP3 Gene Plays a Protective Role in Brucellosis That Is Mediated by the NF-κB Signaling Pathway

Abstract: Naturally occurring functional variants (rs148314165 and rs200820567, collectively referred to as TT>A) reduce the expression of the tumor necrosis factor alpha-induced protein 3 (TNFAIP3) gene, a negative regulator of NF-κB signaling, and predispose individuals to autoimmune disease. In this analysis, we conducted a genetic association study of the TT>A variants in 1,209 controls and 150 patients with brucellosis, an infectious disease, and further assessed the role of the variants in brucellosis. Our data de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…One SNP associated with SLE is present in the coding region of TNFAIP3 and causes a missense mutation that reduces A20 function ( 26 ). Some of the risk SNPs near the coding regions of the TNFAIP3 gene have been shown to reduce both A20 mRNA and protein expression ( 48 ). In our previous study, a significantly increased prevalence of the TC genotype at rs9494885 was found in BD patients, but the TC genotype had no influence on A20 mRNA expression in PBMCs ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…One SNP associated with SLE is present in the coding region of TNFAIP3 and causes a missense mutation that reduces A20 function ( 26 ). Some of the risk SNPs near the coding regions of the TNFAIP3 gene have been shown to reduce both A20 mRNA and protein expression ( 48 ). In our previous study, a significantly increased prevalence of the TC genotype at rs9494885 was found in BD patients, but the TC genotype had no influence on A20 mRNA expression in PBMCs ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins associated with fibrinogen are essential in the aggregation of leukocytes and cellular remodelling. These proteins play an essential role in old mononuclear phagocytes and damages caused by coagulation or fibrinolysis in inflamed tissues [3].…”
Section: Introductionmentioning
confidence: 99%